2022
DOI: 10.1371/journal.pone.0279963
|View full text |Cite
|
Sign up to set email alerts
|

Association between COVID-19 pandemic declaration and depression/anxiety among U.S. adults

Abstract: Background Although studies have investigated the impact of the COVID-19 on mental health, few studies have attempted to compare the prevalence of depression/anxiety symptoms among U.S. adults before and after the COVID-19 pandemic declaration. We examined the prevalence and association between depression/anxiety symptoms and COVID-19 pandemic declaration among U.S. adult population and subgroups. Methods A nationally representative cross-sectional study of the Health Information National Trends Survey (HINT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
1
2
0
Order By: Relevance
“…However, whilst gender remained statistically significant in Model 2, the addition of the COVID-19-related variables (physical and mental health status and contact with friends) and identifying as non-heterosexual were more important in predicting poor mental health than gender. The finding that young people who identify as non-heterosexual have poorer mental health than their heterosexual peers offers support for previous research which found poorer mental health among this vulnerable group both pre- and post-pandemic [ 28 , 29 , 30 , 31 ]. One of the key findings emerging from Model 2 was that young people who felt that their mental health had worsened over lockdown had lower GHQ-12 scores than their peers who thought their mental health had stayed the same or improved.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…However, whilst gender remained statistically significant in Model 2, the addition of the COVID-19-related variables (physical and mental health status and contact with friends) and identifying as non-heterosexual were more important in predicting poor mental health than gender. The finding that young people who identify as non-heterosexual have poorer mental health than their heterosexual peers offers support for previous research which found poorer mental health among this vulnerable group both pre- and post-pandemic [ 28 , 29 , 30 , 31 ]. One of the key findings emerging from Model 2 was that young people who felt that their mental health had worsened over lockdown had lower GHQ-12 scores than their peers who thought their mental health had stayed the same or improved.…”
Section: Discussionsupporting
confidence: 74%
“…A lack of support during COVID-19 lockdowns has also been proposed as one explanation for the higher rate of mental ill-health found among populations identifying as non-heterosexual compared to their heterosexual counterparts [ 12 , 28 , 29 ]. The vulnerability of this marginalised group in terms of pre-pandemic mental health has been well-documented as has their increased risk of social exclusion and violence as a result of COVID-19 [ 29 , 30 , 31 ]. For example, research carried out among adults, pre-pandemic, showed a higher rate of prevalence of common mental disorders among those identifying as non-heterosexual [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation